A study on the effects of potassium borohydride in pulp and paper production from black locust (Robinia pseudoacacia L.) wood - Ahmet Tutuş; Saniye Erkan; Mustafa Çiçekler (Turkish Journal of Forestry, 2021)
In this study, the effects of potassium borohydride (KBH4) added to the cooking liquor (white liquor) in pulp and paper production from black locust (Robinia pseudoacacia L.) woods on the chemical, physical and optical properties of the pulp were investigated. Soda (NaOH) method, which is one of the environmentally friendly cooking methods, was used in the pulp production from R. pseudoacacia woods. By adding 0, 0.3, 0.5 and 0.7% KBH4 to the white liquor, four different cooking experiments were carried out. The yields, kappa numbers and viscosity values of the pulps were measured with the relevant standards. Test papers were produced from each pulp and their physical and optical properties were determined. With 0.7% KBH4 added to the cooking solution, the total yield and viscosity increased by 9.54% and 10.4%, respectively compared to KBH4-free pulp, while the kappa number decreased by 9.48%. As a result of statistical analysis, it has been observed that there is no significant difference between the physical and optical properties of the papers produced from KBH4-free and KBH4-added pulps. Consequently, it was concluded that adding KBH4 to the white liquor in the pulp production from R. pseudoacacia wood with soda method, positively affected the chemical properties of the pulps and did not have a significant effect on the physical and optical properties.